Goat Population Number Simulation and Breeding Parameter Estimation at UPTD BPPTDK, Yogyakarta - Shidana, Muhammad Asyroful Wildan; Maharani, Dyah; Panjono, Panjono (Faculty of Animal Science, Universitas Gadjah Mada, 2025)
Goats farming plays a vital role in ensuring food security and boosting rural incomes, especially in Yogyakarta Special Region. Saanen, Sapera, and Bligon goats are important breeds because of their significant economic value in both meat and milk production. For sustainable development, precise estimates of population trends, breeding factors, and income are essential for effective management and policy formulation. This study aims to estimate the population number of goats, breeding parameters, and gross income over the next five years. The research was conducted from July to September 2024 at The Regional Technical Implementation Unit of the Animal Diagnostic Livestock Breeding Development Center (UPTD BPPTDK) under the Department of Agriculture and Food Security, Special Region of Yogyakarta. The data collected includes both primary and secondary data. Primary data was obtained through direct interviews with staff and management at UPTD BPPTDK-DPKP of the Special Region of Yogyakarta. In contrast, secondary data comprised the latest 2024 population statistics obtained from UPTD BPPTDK. This data served as the basis for simulating population growth and calculating breeding parameters for the next five years. Based on the simulation results, the population of Saanen goats increased, with the percentage increase in livestock population from 2024 to 2028 reaching 125% for Saanen goats, 105% for Sapera goats, and 122% for Bligon goats. The average natural increase (NI) over five years was 40.70% for Saanen goats, 43.93% for Sapera goats, and 44.52% for Bligon goats. The net replacement rate (NRR) for male Saanen goats was 319.2% and for females 211.80%; for male Sapera goats, 453.51% and females 208.92%; for male Bligon goats 517.01% and females 209.68%. The total output, or number of goats that can be sold over five years, was 399, 138, and 432 for Saanen, Sapera, and Bligon goats, respectively. The gross income over five years was IDR 2,738,350,000. Based on these results, proper livestock management at UPTD BPPTDK-DPKP DIY can lead to increased and balanced goat populations over the next five years. These estimations can be used to inform policy decisions for livestock development programs at UPTD BPPTDK-DPKP DIY.